Attitudes towards patient safety culture among postgraduate nursing students in China: A cross-sectional study. (July 2019) - Kong, Ling-Na; Zhu, Wen-Fen; He, Shan; Chen, Shuo-Zhen; Yang, Li; Qi, Li; Peng, Xin
Abstract: Patient safety is crucial to healthcare quality. It is important to assess the nursing students' safety attitudes to identify the weaknesses for developing education program and fostering students' engagement in patient safety practices. This study aimed to assess attitudes towards patient safety culture among postgraduate nursing students in China, and explore the factors that affect their safety attitudes and the relationships of safety attitudes and safety-related behaviors. This study used a cross-sectional survey design. A convenience sample of 231 postgraduate nursing students from ten medical universities in China completed the Chinese version of Safety Attitude Questionnaire, including six domains: teamwork climate, safety climate, perceptions of management, job satisfaction, working conditions and stress recognition. The mean scores of the six domains ranged from 65.22 to 70.75 on a 100-point scale. Percentages of positive responses for the six domains were below 55%, with the two lowest percentages for working conditions (35.9%) and safety climate (30.7%). Significantly lower domain scores were found in students with younger age, no work experience, higher workload and received safety education. There were positive correlations between the six domains and safety-related behaviors except for stress recognition. Nursing educators should focus more on the improvement of patient safety education and establishment of supportive work environment to enhance postgraduate nursing students' attitudes towards safety culture. Highlights: Postgraduate nursing students had low positive attitudes towards patient safety culture. Safety attitudes affected by age, work experience, workload and safety education among postgraduate nursing students. Students' safety attitudes were related to their safety-related behaviors. Patient safety education should be emphasized to enhance their safety attitudes. Supportive work environment should be provided for nursing students.